Technology, Society, and Social Control in Le Corbusier's Citè de Refuge, Paris 1933 - Taylor, Brian Brace
Tecnología, sociedad y control social en la Cité de Refuge de Le Corbusier, París, 1933.
Keywords: LE CORBUSIER; FRANCIA; PARIS; HISTORIA; REFUGIOS